Multiresistant Plasmids from Pseudomonas aeruginosa Highly Resistant to Either or Both Gentamicin and Carbenicillin - Kontomichalou, Polyxeni (1976)
High-level resistance to gentamicin and carbenicillin was found in 30 and 10.7%, respectively, of Pseudomonas aeruginosa strains, especially in isolates from urine. In 23 out of 25 strains tested, these resistances were R mediated and linked to multiresistant plasmids, carrying genes for resistances to five other aminoglycosides, tobramycin, kanamycin, neomycin, streptomycin, and spectinomycin, and for resistances to chloramphenicol, tetracycline, sulfonamides, and mercury chloride. Carbenicillin resistance was unstable in Pseudomonas, and in its presence the multiresistant plasmids had a host range extended to the Enterobacteriaceae (group I plasmids). Otherwise they were transferable intragenerically only (group II plasmids). The extended host range plasmids were, as a rule, in fi(−) incompatibility class A–C. Segregants incompatible with both class A–C and P plasmids were detected. The β-lactamase specified by the carbenicillin marker was of the TEM-like type. Multiple linkages of resistance determinants to the aminoglycosides were concomitantly present in most of the plasmids. Results from the bioassay indicated the presence of at least two aminoglycoside-inactivating enzymes.